La vita fattiva nell’esperienza del protocristianesimo - Mora, Francesco (Bollettino Filosofico, 2020)
In Ws 1920/21 Heidegger examines the experience of factical life within the Letters of Saint Paul to the Galatians and Thessalonians. The present essay tries to clarify the meaning of factical life and facticity in the early Christian communities. At the same time, it analyses Heidegger’s relationship with contemporary Christian-Protestant thought, and emphasizes the importance that must be attributed to religion. These problems are at the basis of the hermeneutics of facticity and can fit differently within the existentials of Being and time. Keywords: Critique of Historicism, Factical Life, Parousia, Phenomenology of Religion, Theoretic Knowledge